Muslim Minorities in the Context of Citizenship in Western Countries According to Fiqh al-Aqalliyat; Challenges and Obligations - Khoirul Anwar; Hilmi Ridho; Muhammad Sibawaihi; Muhamad Sofi Mubarok; Aizat Khairi (Tribakti: Jurnal Pemikiran Keislaman, 2025)
In reality, the Muslim population in Western countries is increasing significantly every year. By 2030, it is projected that the world's Muslim population will reach 2.2 billion with a growth rate of 24.9%. Muslims living in Western countries live their lives as a minority group, they are faced with various complex challenges, ranging from worship issues, and muamalah, to marriage issues. This paper aims to examine the development, challenges, and problems faced by Muslim minorities living in Western countries, and how fiqh responds in providing solutions to all issues faced by Muslim minorities living in non-Muslim majority areas. This research method uses normative legal research, namely legal research that focuses on analyzing the text of laws and regulations, legal decisions, or other legal sources. The primary data is taken from classical and contemporary books, books, and reputable journals that discuss the problems of Muslim minorities in non-Muslim majority countries. The results of this study show that the presence of Muslims in Western countries poses a major challenge, namely changing the negative views of Western countries towards Islam which is considered an extreme and terrorist religion. Four serious issues are often faced by Muslim minorities: eating food slaughtered by non-Muslims, receiving inheritance from non-Muslims, marital relations between people of different religions, and wishing non-Muslims happy holidays. Although there is still debate among scholars regarding the issue of 'food from non-Muslim slaughter', they choose not to allow consuming food from non-Muslims based on the rule of shad al-zari'ah (closing opportunities). Apart from this, in the context of citizenship, Muslim minorities have six obligations towards the state, namely preaching, implementing basic religious laws, maintaining Islamic law, assisting the development of the state, establishing good relations between communities, and not rebelling against the state.